Anteseden yang memengaruhi minat beli ulang: Studi pada konsumen produk Mie Sedaap di Jawa Tengah - Dina Kurniawati; Budi Hartono; Shinta Ratnawati (Journal of Management and Digital Business, 2025)
Instant noodle consumption has increased every year, both in Indonesia and worldwide. Ease of consumption, good taste, and the ability to be incorporated into various foods make instant noodles very popular with the public. Various instant noodle brands are also required to continue innovating to avoid losing market share. One of the brands known to Indonesians is Mie Sedaap. This study aims to determine the effect of brand awareness, brand image, brand loyalty, and perceived quality on repurchase intention in consumers of Mie Sedaap products in Central Java. The sampling technique in this study was purposive, with 162 respondents who were consumers of Mie Sedap in Central Java. The results of the study indicate that brand awareness has a positive and significant effect on repurchase intention, that brand loyalty has a positive and significant effect on repurchase intention, and that perceived quality has a positive and significant effect on repurchase intention. However, brand image has a negative and significant effect on the repurchase intention of Mie Sedaap consumers in Central Java. These results indicate that Mie Sedaap needs to pay attention to its image, which can be achieved by improving the quality of its products to meet consumer expectations better.